Dinuclear Face‐Sharing Bi‐octahedral Tungsten(VI) Core and Unusual Thermal Behavior in Complex Th Tungstates. Issue 21 (27th March 2015) - Xiao, Bin; Gesing, Thorsten M.; Robben, Lars; Bosbach, Dirk; Alekseev, Evgeny V.
Abstract Invited for the cover of this issue are the groups of Evgeny V. Alekseev at the Forchungszentrum Jülich and Thorstem M. Gesing at the University of Bremen. The image depicts the complex thorium tungstate polyanions, having a six‐leafed lily cross‐section, containing a rare confacial [W2O9]6− bioctahedral core. Read the full text of the article at 10.1002/chem.201500500.